Analisis Kelayakan Usaha Air Minum dalam Kemasan PT. Amiro di Desa Uma Jero, Kecamatan Busungbiu, Kabupaten Buleleng - NI KETUT PURANI WIYANTI; I WAYAN BUDIASA; I NYOMAN GEDE USTRIYANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Analysis of Business Feasibility Study in Bottled Drinking Water of PT.Amiro in Uma Jero Village, Busungbiu District, Buleleng Regency.Water is a major component in the human body, without which creatures cannotgrow and develop. Drinking water is a major component of the body; on averageeach person has 70-80 percent of water from his body weight. The community hasnow switched from consuming ordinary drinking water which is cooked intobottled water. Companies engaged in the BDW sector keep increasing andcontinue to expand their product networks. The purpose of this study was todetermine the bottled drinking water business at PT. Amirowhether it isfinancially feasible in terms of investment criteria, namely NPV, IRR, Net B / C,Payback Period and Sensitivity Analysis and the goal of the study was also toidentify the constraints faced by PT. Amiro in running a business. Based on thisresearch, it could be seen that the NPV value wasRp. 12,640,670,205, IRR35.79%, Net B / C 3.64, and the Payback Period was 8 years 3 months, thereforeit means that BDW business of PT. Amirois financially feasible to be carried out.Constraints in the feasibility study of PT. Amiro, in developing the businessprocess were that the licensing process took a lot of time to meet the requirementsneeded to obtain a business license such as the Agency of Food and Drug Control,Indonesian National Standard, Halal Certificate from MUI and ISO 9001. Amirois a new player in the BDW business and is not yet known by the public so itneeds a strategy to get market share from a very dense market.